2010
DOI: 10.1243/09544097jrrt282
|View full text |Cite
|
Sign up to set email alerts
|

Tilting Trains: Benefits and Motion Sickness

Abstract: Carbody tilting is today a mature and inexpensive technology that allows higher speeds on curves, thus shortening travel time. The technology has been accepted by many train operators, but some issues are still holding back the full potential of tilting trains. This paper focuses on improving the benefits and limiting the drawbacks of tilting trains. This is done by quantifying the possible running time benefits compared with today's tilting trains, identifying what motion components have an influence on motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…Tilt is executed by actuators which may be hydraulic or electromechanical in nature. Also the centre of gravity does not change its position thus it is considered a much safer alternative to the passive tilt system [10]. Control systems are installed in order to initiate tilt in a timely fashion so as to efficiently utilise the vehicle capabilities.…”
Section: Passively Tilted Trains 2 Actively Tilted Trainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tilt is executed by actuators which may be hydraulic or electromechanical in nature. Also the centre of gravity does not change its position thus it is considered a much safer alternative to the passive tilt system [10]. Control systems are installed in order to initiate tilt in a timely fashion so as to efficiently utilise the vehicle capabilities.…”
Section: Passively Tilted Trains 2 Actively Tilted Trainsmentioning
confidence: 99%
“…In a survey done in 1964, it was reported that 0.13 % out of 370,000 individuals suffered symptoms related to motion sickness on non-tilting trains in America, whilst on a similar test in Tokyo, 18 % of passengers experienced motion sickness symptoms [3]. Conflicting test reports have also been noticed in reports by Frostberg on tests in Sweden (Swedish X2000 tilting train) and Norway where the Swedish report claimed that there was a clear correlation between tilt compensation and motion sickness, whilst the Norway report claimed that there was no significant correlation between tilt compensation and motion sickness [10,22]. Persson [10] also claims that the extent of reported cases in Europe seems to be less than those reported in Japan.…”
Section: Motion Sickness In Trainsmentioning
confidence: 99%
“…Fig. 6 The basic concept of tilting trains [3] Super-elevations applied for conventional train's (left) and tilting train's (right) passing curve for cant deficiency, applied to Swedish tilting trains [4]. This decision was based on the assessment that those values would not adversely affect to passengers' comfort.…”
Section: Minimum Curve Radiusmentioning
confidence: 99%
“…About 9% running time may be saved if trains and speed profiles are improved [18]. Maintaining the original control would not only require a larger maximum tilt angle, but would also result in an increased risk of motion sickness.…”
Section: Improved Speed Profilesmentioning
confidence: 99%